Induction of nitric oxide synthase and microvascular injury in the rat jejunum provoked by indomethacin. - Whittle, B. J. (1995)
1. The role of nitric oxide (NO) formed by the inducible isoform of NO synthase (NOS) in the generation of indomethacin-induced intestinal microvascular leakage was investigated in the rat. 2. Indomethacin (10 mg kg-1, s.c.) provoked an elevation of vascular leakage of radiolabelled human serum albumin in the jejunum over 48 h, commencing 18 h after its administration. This was associated with the induction of a calcium-independent NOS, as assessed by the conversion of radiolabelled L-arginine to citrulline. 3. Pretreatment with the glucocorticoid, dexamethasone (1 mg kg-1 day-1, s.c.) inhibited the induction of NOS and reduced jejunal microvascular leakage, determined 24 and 48 h after indomethacin. 4. Administration of the broad-spectrum antibiotic, ampicillin (800 mg kg-1 day-1, p.o.) likewise inhibited both the induction of NOS and the plasma leakage observed 24 and 48 h after indomethacin. 5. Ampicillin pretreatment did not, however, inhibit the induction of NOS, determined 5 h following endotoxin (3 mg kg-1 i.v.) challenge. Furthermore, incubation with ampicillin (1 mM, 10 min) did not inhibit the activity of the calcium-independent isoform in vitro. 6. Administration of the NOS inhibitor, NG-nitro-L-arginine methyl ester (L-NAME, 2-10 mg kg-1, s.c.), at the time of the detectable expression of the inducible NOS (18 h after indomethacin), dose-dependently attenuated the plasma leakage, determined 6 later. This effect was reversed by pretreatment with L-arginine (300 mg kg-1, s.c.) 15 min before L-NAME. 7. These findings suggest that induction of a calcium-independent NOS following indomethacin administration involves gut bacteria and leads to microvascular injury in the rat jejunum.